High‐Resolution Intrashell Oxygen Isotope Studies of Cathaica fasciola and Bradybaena ravida Land Snails and Their Environmental Implications - Qianya Li; Jibao Dong; Hong Yan; Huayu Huang; Xiulan Zong; Guozhen Wang; Chengcheng Liu; Yunning Cao; Weiguo Liu; Zhisheng An (Geophysical Research Letters)
Abstract Intrashell oxygen isotope (δ18Os) analyses of terrestrial snails have been carried out over two decades. However, the intraspecies/interspecies differences are not yet well understood. Here, we conducted a high‐resolution intrashell δ18Os study on 43 shells from Cathaica fasciola and Bradybaena ravida, and 1449 δ18Os data were obtained. These large amounts of data demonstrate the reproducibility of intrashell δ18Os. Our results suggest that C. fasciola and B. ravida have similar growing seasons mainly from March to October in the studied region. The ecological habits of the two species could explain the distinctive variations in their δ18Os sequences. Therefore, our study may interpret the discrepancy between the studies of land snail species and the stable/clumped isotopes of their shells. Moreover, the calculated average growth rate is ∼290 μm/day (from 250 to 330 μm/day) for nonadult C. fasciola. Thus, the use of snail shells for reconstructing high‐resolution terrestrial climate changes is promising.